2010
DOI: 10.1007/s10853-010-4323-9
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy investigation on the hydration degree of a cement paste

Abstract: NIR Infrared spectroscopy is a fast and easy-to-perform technique characterized by a high sensitivity towards water containing systems and for this reason it is a suitable tool for investigating structural modifications of hydrating cementing materials, even if the lack of knowledge in this field makes the interpretation of NIR vibrational bands very difficult.In this paper the NIR spectrum of a hydrated ordinary Portland cement is deeply investigated and an interpretation of the different bands is proposed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The 4500–5800 cm −1 region contains combination bands of water and surface P–OH (Table II). 12,13,31,34 We found that the water band, located in the 4600–5400 cm −1 range, is broad and asymmetric, with extra features indicative of its inherent complex structure (Fig. 1b).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The 4500–5800 cm −1 region contains combination bands of water and surface P–OH (Table II). 12,13,31,34 We found that the water band, located in the 4600–5400 cm −1 range, is broad and asymmetric, with extra features indicative of its inherent complex structure (Fig. 1b).…”
Section: Resultsmentioning
confidence: 92%
“…24,–27 For the synthetic apatites, they are dominated by bands of water and various OH groups. 12,13,31,34 Figure 1a shows the spectra of samples HA100–HA800. There are three main spectral regions to discuss: 4500–5800, 6200–8000, and 10 000–10 500 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is essential to: (i) quantify the carbonation reaction products, (ii) control the carbonation process and (iii) understand its effects on the cement integrity and properties. Thus, techniques such as phenolphthalein test, X-ray florescence (XRF), X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray microtomography (MicroCT), thermogravimetric analysis (TGA), nuclear magnetic resonance (NMR) spectroscopy and infrared (IR) spectroscopy are widely applied in the literature to characterize carbonated cementitious materials and their composites [32,[35][36][37][38]. Among the characterization methods, the analysis of CaCO 3 in cementitious materials can be performed in the following way: (i) qualitative, by means of phenolphthalein, TEM and SEM methods, (ii) semi-quantitative, using the IR, MicroCT, XRD and XRF instruments and (iii) quantitative, through TGA analysis [11,[35][36][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In this region three bands (or groups of bands) can be identified. The feature between 7000 and 7300 cm −1 is the first OH overtone (2ν 1 , 2ν 3 , and ν 1 + ν 3 ) and it has many components [ 32 , 33 ]: one easily detectable at 7083 cm −1 corresponding to OH stretching vibrations in portlandite, a broader but less precise shoulder at 7200 cm −1 related to C–S–H gel and a band around 7100 cm −1 related to the presence of Al-bonded O–H groups in ettringite. Although the overlapping of these bands/shoulders complicates the identification of the three components, the portlandite band is only recognizable in the Ref paste where increases its intensity from 2 to 90 d. However, in the low-pH cement pastes this band is not easily detectable and a very broad band related to structural water in C–S–H gels is observed, confirming the CH consumption.…”
Section: Resultsmentioning
confidence: 99%